Underwater light attenuation inhibits native submerged plants and facilitates the invasive co‐occurring plant Cabomba caroliniana. (31st January 2023) - Huang, Xiaolong; Ke, Fan; Lu, Jing; Xie, Hongmin; Zhao, Yu; Yin, Chunyu; Guan, Baohua; Li, Kuanyi; Jeppesen, Erik
Abstract: Aim: Decreasing in the diversity and distribution of native submerged plants have been widely observed in recent decades. Global underwater darkening, which is mainly caused by radiation dimming and a decrease in transparency due to, e.g. eutrophication, has emerged as a general trend that strongly hampers the growth of submerged plants in lakes by decreasing the light available for photosynthesis. However, few studies have attempted to compare the responses of native and invasive submerged plants to underwater darkening. In this study, we aimed to compare the effects of light attenuation on the growth and photosynthesis traits of native and invasive submerged plants. Location: East China. Method: Through field investigations and a mesocosm experiment, the responses of functional traits of two representative native [water thyme ( Hydrilla verticillata ), Eurasian watermilfoil ( Myriophyllum spicatum )] and one invasive [Carolina fanwort ( Cabomba caroliniana )] plant species to various environmental factors, notably to underwater light attenuation, were studied. Results: Underwater photosynthetically active radiation (PAR) exerted a substantial effect on the relative coverage and abundance of the three studied submerged plants in their natural freshwater habitats. Invasive C. caroliniana showed relatively superior growth (total biomass and relative growth rate) and photosynthesis traits (maximum quantum yield of photosystem II F v / F m, chlorophyll a content, chlorophyll b content and the ratio of Chl a and b contents) compared to the two native plants under low underwater PAR conditions. In contrast, under high underwater PAR conditions, C. caroliniana showed the opposite response. Main Conclusions: Light attenuation inhibits the growth of native submerged plants but facilitates the growth of invasive plant species. Restoration of freshwater lakes by reducing deterioration from underwater darkening (for instance, by reducing of external nutrients loading) may therefore constrain the growth and spread of the invasive C. caroliniana .